Analysis Of Tensile Strenghth Coconut Coir Fiber Composit Using The Vaccum Bagging Method - Ilhami, Zaqi Arya Zullfawas; Setiawan, Ferry; Sehono, Sehono (Journal of Metallurgical Engineering and Processing Technology, 2024)
Abstract The utilization of coconut fiber currently is limited to making brooms or for burning, necessitating further applications. One of these applications is its use as a reinforcement in composites, enhancing utility value and environmental friendliness. This study focuses on crafting composites from coconut fiber with variations in fiber orientation: random, 0°, and 45°.Tensile testing results reveal that the random fiber orientation variation exhibits the best performance, with a stress of 27.30 MPa, attributed to higher density. The 45° fiber orientation variation has the lowest stress (24.23 MPa) due to a lower fiber count. In bending tests, the random fiber orientation variation again performs the best, with a bending stress of 120 MPa, attributed to its high density that strengthens the structure. The 0° fiber orientation has the lowest bending stress (88.59 MPa) due to lower fiber density.Overall, utilizing coconut fiber as reinforcement in composites shows promising positive outcomes, with the random fiber orientation variation providing the best mechanical performance. This endeavor holds the potential to enhance the economic and ecological value of coconut fiber.Keywords: Composite, fiber, coconut, tensile, bending